LOBYARD Sdn Bhd / Muhammad Faris Danial Mohamad Fauzi - Mohamad Fauzi, Muhammad Faris Danial (2020)
LOBYARD SDN BHD offers the best Lobster that are produce from the backyard of our for house to the customer, we providing the high quality, fresh, clean, pure and Halal Lobster which can give satisfaction towards the consumer. We produce a Healthy and safe product which can fulfill the wants of the consumer. This business is based on partnership with four (4) leaders holding crucial position in the organization, along with Mr Muhammad Faris Danial Bin Mohamad Fauzi as the General Manager, Mr Afnan Hasuna Bin Mohamad Hanafi as the Marketing Manager, Mr Muhammad Arif Akmal Bin Mohamad Haris as the Operational Manager, Mr MuhammadAmir Hadi Bin Abdul Rahim as the Financial Manager and Ms Nabilah Iman Binti Mohd Roslan as the Administrative Manager. The main objective of this company are to give a solution to the issue related to the other company that use non-halal substance to produce lobster, we will make sure that our company will consistently producing and providing Halal Fresh Lobster product to make sure the consumer safety is secured from any dangerous, hazardous and harmful substance and also to fulfill their wants. So to meet the consumer fulfillment, we will be operating and producing the product that can satisfy the taste and desire required of consumer competently and inconsistently. We are also want to give the best and high quality product so we are able to gain their trust and loyalty.